Mediation of transactive memory capability in relationship of social media usage and job performance - Feng, Tao; Madni, Ghulam Rasool (Frontiers in Psychiatry, 2024)
This study explores the role of transactive memory capability as a mediator in the relationship between social media usage and job performance. Drawing on transactive memory theory, we hypothesized that individuals who use social media more intensively for task-oriented purposes and relationship building are more likely to develop transactive memory capability, which in turn enhances their job performance. A survey was conducted among 816 employees in China from various industries to collect data on their social media usage patterns, transactive memory capability, and job performance. Results from structural equation modeling indicate that social media usage has a positive impact on job performance. Additionally, transactive memory capability mediates the relationship between social media usage and job performance. This study has contribution in literature by demonstrating the beneficial effects of social media usage on the development of transactive memory capability and job performance. It is suggested that social media usage can be used a valuable tool for enhancing performance of employees. Employees should gain an understanding of how social media fosters the development of transactive memory capability to utilize it more effectively. These findings also suggest that the way individuals use social media can influence their ability to access and share knowledge within their social networks, ultimately impacting their job performance.